Recommendation strategies for the prevention and control of high morbidity of dengue hemorrhagic fever in North Sumatera province - Siregar, Fazidah Aguslina (2016)
Background: The incidence of dengue hemorrhagic fever (DHF) in North Sumatera Province remains high despite effort to control it. Objectives : This study aimed to document information about the adequacy of the current Indonesia surveillance system for DHF and factors responsible for high DHF transmission. These will be used for recommending strategies for the prevention and control for DHF in North Sumatera Province. Material and Methods: Five study designs were adopted in this study. In the exploratory study, all key personnels involved in the surveillance system for DHF at the district and health facility levels in the selected six districts were interviewed to determine the function and performance of the surveillance system. The case cohort study recruited a total of 682 respondents with case: subcohort ratio 1:1. Simple and Multiple logistic regression were applied to determine the factors associated with DHF. For the comparative cross sectional study, 688 households both in high and low incidence district were selected using multistage sampling. Simple and Multiple logistic regression were again applied to determine the factors associated with DHF among the households in districts with high incidence. In the entomology study, Independent T test and Two Way Anova were used to determine the effect of larvae positive containers on DHF transmission, whereas for larvae and adult indices Simple and Multiple logistic regression were applied. Theclimatic study utilises monthly a years climatic (2003-2011) secondary data. The relationship between climatic and dengue hemorrhagic fever incidence was determined by Pearson correlation and the impact of climates on DHF incidence by Time series regression. Seasonal Autoregressive Integrated Moving Average (SARIMA) model was then developed to predict the occurrence of DHF. Results : The structure of DHF surveillance system was good but suboptimum with major deficiencies that include unavailability of guidelines, insufficient resources and poor core and supportive functions. Socio-cultural and environmental factors associated with DHF incidence were investigated through case–cohort and comparative cross sectional studies. Significant factors include experience with DHF in family, travelling history, length of stay, frequency of cleaning water container, frequency of cleaning garbage disposal, education, knowledge, practices in preventive measure, source of drinking water, house style and house with gutter. Aedes larvae and adult indices were above the critical level especially in the high incidence districts with house indices as the predictor for dengue transmission. Climatic factors that include rainfall, rainy days, temperature and relative humidity were significantly associated with DHF incidence. SARIMA model (0,1,1)(0,1,1)12 was able to predict DHF occurrence. Conclusion: The existing surveillance system for DHF need to be strengthened in every aspect. Socio-cultural and environmental factors associated with DHF should be addressed and controlled. Measures should be taken to eliminate or being down the density of Aedes vectors. Climatic factors should be integrated in the national prevention and control program for DHF.